Cancer risks by sex and variant type in PTEN hamartoma tumor syndrome. (28th September 2022) - Hendricks, Linda A J; Hoogerbrugge, Nicoline; Mensenkamp, Arjen R; Brunet, Joan; Lleuger-Pujol, Roser; Høberg-Vetti, Hildegunn; Tveit Haavind, Marianne; Innella, Giovanni; Turchetti, Daniela; Aretz, Stefan; Spier, Isabel; Tischkowitz, Marc; et al.
Abstract: Background: PTEN Hamartoma Tumor Syndrome (PHTS) is a rare syndrome with a broad phenotypic spectrum, including increased risks of breast (BC, 67%-78% at age 60 years), endometrial (EC, 19%-28%), and thyroid cancer (TC, 6%-38%). Current risks are likely overestimated due to ascertainment bias. We aimed to provide more accurate and personalized cancer risks. Methods: This was a European, adult PHTS cohort study with data from medical files, registries, and/or questionnaires. Cancer risks and hazard ratios were assessed with Kaplan-Meier and Cox regression analyses, and standardized incidence ratios were calculated. Bias correction consisted of excluding cancer index cases and incident case analyses. Results: A total of 455 patients were included, including 50.5% index cases, 372 with prospective follow-up (median 6 years, interquartile range = 3-10 years), and 159 of 281 females and 39 of 174 males with cancer. By age 60 years, PHTS-related cancer risk was higher in females (68.4% to 86.3%) than males (16.4% to 20.8%). Female BC risks ranged from 54.3% (95% confidence interval [CI] = 43.0% to 66.4%) to 75.8% (95% CI = 60.7% to 88.4%), with two- to threefold increased risks for PTEN truncating and approximately twofold for phosphatase domain variants. EC risks ranged from 6.4% (95% CI = 2.1% to 18.6%) to 22.1% (95% CI = 11.6% to 39.6%) and TC risks from 8.9% (95% CI = 5.1% to 15.3%) to 20.5% (95% CI = 11.3% to 35.4%). Colorectal cancer, renal cancer, and melanoma risks were each less than 10.0%. Conclusions: Females have a different BC risk depending on their PTEN germline variant. PHTS patients are predominantly at risk of BC (females), EC, and TC. This should be the main focus of surveillance. These lower, more unbiased and personalized risks provide guidance for optimized cancer risk management.